Grouping оf Complexes оf Multiphase Queuing Systems. - G. M. Zholtkevych; Z. F. Nazyrov; S. Y. Ignatov (Kherson State University, 2009)
Issues of classification of the complexes of multiphase queuing system systems in correspondence with entrance-output correlations and automatic grouping of complexes by the analysis of the graph of final product composition is examined in this work.